A new hybrid non-standard finite difference-adomian scheme for solution of nonlinear equations - Moaddy .K,; Hashim .I,; Alomari .A.K,; Momani .S, (Universiti Kebangsaan Malaysia, 2011)
This research develops a new non-standard scheme based on the Adomian decomposition method (ADM) to solve nonlinear equations. The ADM was adopted to solve the nonlinear differential equation resulting from the discretization of the differential equation. The new scheme does not need to linearize or non-locally linearize the nonlinear term of the differential equation. Two examples are given to demonstrate the efficiency of this scheme